2003
DOI: 10.1309/ytu2fuhbexjlwmld
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Protein to Analyze Autoantibodies to Proteinase 3 in Systemic Vasculitis

Abstract: The presence of antineutrophil cytoplasmic autoantibodies with specificity for proteinase 3 (PR3-ANCA) usually is detected by enzyme-linked immunosorbent assay (ELISA) with purified PR3 as a substrate. We studied the technical performance of direct and capture ELISA using a recombinant proteolytically inactive form of PR3 produced in the baculovirus expression system for the detection of PR3-ANCA in 114 patients with systemic vasculitis at diagnosis. We found that ELISA using recombinant PR3 produced in insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Also recombinant PR3 has not been successfully introduced in clinical practice due to problems with expression and purification procedures 20. A direct ELISA using recombinant, proteolytically inactive PR3 produced in the baculovirus expression system, appeared less sensitive than a direct ELISA using native PR3 21. Recombinant PR3, however, is preferentially expressed in human cell lines that constitutively secrete the wild-type precursor, but are unable to generate active PR3 in vivo 8 22.…”
Section: Discussionmentioning
confidence: 99%
“…Also recombinant PR3 has not been successfully introduced in clinical practice due to problems with expression and purification procedures 20. A direct ELISA using recombinant, proteolytically inactive PR3 produced in the baculovirus expression system, appeared less sensitive than a direct ELISA using native PR3 21. Recombinant PR3, however, is preferentially expressed in human cell lines that constitutively secrete the wild-type precursor, but are unable to generate active PR3 in vivo 8 22.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the PR3 N-terminus is an element of the PR3-NB1 binding site. Studies using recombinant PR3 demonstrated that nearly all ANCA sera from patients with vasculitis recognize PR3 irrespective of its N-terminus [30,31,[47][48][49]. In fact, clinical data show that ANCA binding not only to mature PR3 but also to proPR3 have the same or even better predictive power for disease progression in patients with ANCA vasculitis [8,50].…”
Section: Discussionmentioning
confidence: 99%
“…Here, for the first time, we used a flow cytometric approach to measure early detectable (actin polymerization) and late detectable (oxidative burst) responses of neutrophils [36] to anti-PR3 antibody at the single-cell level in relation to PR3 expression on the neutrophil surface. In our system, we only used the monoclonal anti-PR3G-3 as a model antibody for activation of neutrophils because of its adequate binding characteristics in capture ELISA in comparison with other PR3-specific mAb such as mAb 12.8 [37]. We also measured F-actin responses with PR3-ANCA-positive IgG fractions from patients with active WG (Fig.…”
Section: Discussionmentioning
confidence: 99%